Who Drives the Agenda: Media or Parties? A Seven-Country Comparison in the Run-Up to the 2014 European Parliament Elections. (January 2019) - Jansen, A. Severin; Eugster, Beatrice; Maier, Michaela; Adam, Silke
In this paper, we examine who drives attention to the European Union (EU) in member nations—the media or the parties—and how cross-national variations in these media-party interactions can be explained by focusing on issue salience in campaign communications, party polarization, and media system characteristics. To answer these questions, we rely on a quantitative content analysis of newspaper articles and party press releases in seven countries (Austria, France, Germany, Greece, the Netherlands, Portugal, and the United Kingdom) during the twelve weeks prior to the 2014 European Parliament (EP) election. Our results from a daily-level vector autoregression (VAR) analysis show that parties are the main driver. However, our findings also indicate that single approaches in comparative research, namely, issue salience, party polarization, and media characteristics, cannot fully explain cross-national variations, which stem from combinations of different determinants, such as low (high) EU issue salience interacting with high (low) party polarization.